Measured MIMO capacity and diversity gain with spatial and polar arrays in ultrawideband channels - Malik, W; Edwards, D (2007)
This paper experimentally investigates the performance of multiple-input multiple-output (MIMO) systems in indoor ultrawideband (UWB) channels. The improvement in robustness and information rate due to spatial and polar antenna arrays is evaluated. The subchannel correlation, power gains of supported eigenmodes, and branch power ratios are analyzed. The polar arrays are found to experience lower correlation than that of spatial arrays. SNR gains of up to 3 and 5 dB are reported with 1 × 2 and 1 × 3 spatial arrays, respectively; the latter is shown to double the coverage range. The mutual information capacity is found to scale almost linearly with the MIMO array size, with very low variance. It is confirmed that the device compactness achieved by the polar array comes with only a small penalty in the achievable capacity and SNR gain compared to the spatial array. The multiple-antenna UWB techniques explored in this paper offer the potential for high-data-rate, robust communications. © 2007 IEEE.